2013
DOI: 10.1088/2041-8205/763/2/l29
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Discovery of the Debris Disk Around Hip 79977

Abstract: We present Subaru/HiCIAO H-band high-contrast images of the debris disk around HIP 79977, whose presence was recently inferred from an infrared excess. Our images resolve the disk for the first time, allowing characterization of its shape, size, and dust grain properties. We use angular differential imaging (ADI) to reveal the disk geometry in unpolarized light out to a radius of ∼2 ′′ , as well as polarized differential imaging (PDI) to measure the degree of scattering polarization out to ∼1. ′′ 5. In order t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
71
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 47 publications
12
71
0
Order By: Relevance
“…i.e., those fulfilling 2 c min 2 c + N 2 data binned (Thalmann et al 2013), which for our case implies 2 c n 1.124. The best-fit model accurately reproduces the disk morphology (Figure 2) and, when subtracted from the Keck image, nulls its signal, including the point-source-like peak, but leaves the hook-like features largely intact (SNRE ∼ 3.5-4.5 in the residual image).…”
Section: Disk Forward Modelingmentioning
confidence: 74%
“…i.e., those fulfilling 2 c min 2 c + N 2 data binned (Thalmann et al 2013), which for our case implies 2 c n 1.124. The best-fit model accurately reproduces the disk morphology (Figure 2) and, when subtracted from the Keck image, nulls its signal, including the point-source-like peak, but leaves the hook-like features largely intact (SNRE ∼ 3.5-4.5 in the residual image).…”
Section: Disk Forward Modelingmentioning
confidence: 74%
“…The ADI technique complemented by principal component analysis (PCA) is then used, which reconstructs the PSF of the central star from a library of reference PSFs and subtracts it from the target image (Soummer et al 2012). This is the so-called PCA-ADI technique that permits forwards modelling of astronomical sources, such as circumstellar disks, which in some cases has proven better at removing certain systematic noise patterns (see Thalmann et al 2013) than the locally optimized combination of images (LOCI, Lafrenière et al 2007) and seems to yield similar S/N images (e.g. Meshkat et al 2013).…”
Section: Angular Differential Imagingmentioning
confidence: 99%
“…The ADI approach is completed by derotating all the images according to their individual parallactic angle and collapsing them together into one single final PCA-ADI image for every subtracted mode. The mean is used in our reduction instead of the median to assure linearity of the data (Thalmann et al 2013;Brandt et al 2013). After visual inspection of the output images, we concluded that the subtraction of five modes out of 53 provides a good balance between flux self-subtraction and speckle noise suppression.…”
Section: Angular Differential Imagingmentioning
confidence: 99%
“…For highly inclined and well resolved circumstellar disks, the radial noise profile can be measured in sectors of the final science image unaffected by the disk flux (e.g., Thalmann et al 2011Thalmann et al , 2013. However, the crescent of scattered light from the LkCa 15 disk, as well as the surrounding oversubtraction regions, dominate our ADI images at all position angles, which renders it impossible to measure an unbiased noise profile.…”
Section: Noise Estimationmentioning
confidence: 99%
“…For point sources, this effect is easy to determine (e.g., Lafrenière et al 2007;Brandt et al 2013), but the subtraction effects are non-trivial for extended sources such as disks and can affect the apparent morphology of the source. Forward modeling is a powerful tool for interpreting these images and extracting the disk geometry (e.g., Thalmann et al 2011Thalmann et al , 2013Milli et al 2012).…”
Section: Introductionmentioning
confidence: 99%